Surgical versus non-surgical intervention in endometriosis with infertility: a patient preference trial - Ishrat, Shakeela; Rupa, Shamima Bashar; Hossain, Marufa; Anwary, Shaheen Ara; Deeba, Farzana; Banu, Jesmine (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Hormonal suppression decrease pain and reduce endometrioma size in women with endometriosis. There are medications like cabergoline which reduce inflammation associated with endometriosis but do not prevent ovulation. Hormonal suppression followed by cabergoline may allow pregnancy in women with endometriosis. The objective of the study was to assess and compare the efficacy of medical versus surgical management in infertile women with endometriosis. Methods: A patient preference clinical trial was carried out on 20 women who wish pregnancy and has sonographic evidence of endometrioma and pain. They were counseled adequately about the advantages and disadvantages of surgical and medical management of endometriosis with infertility and were asked to make a choice. The interventions were applied according to patient preference. The interventions were i) dienogest for 3 months when cyst size ≤5 cm and letrozole plus norethisterone for 6 months when cyst size > 5 cm followed by cabergoline 0.5 mg twice weekly for 6 months, plus timed intercourse and ii) laparoscopic surgery followed by expectant management or ovarian stimulation with or without intrauterine insemination. The women were followed up for results. Results: A total of 18 participants opted for medical management and only 2 participants for surgery. All participants given medical management had reduction of pain, and all except one had reduction of cyst size. Pregnancy occurred in 2 out of 14 (14.3%) participants given medication. One woman with surgery had persistence of pain and recurrence of cyst. No one having surgery got pregnant during the study period. Conclusions: The infertile women with endometriosis prefer medical management over surgery. The medical management may be a better option for infertile women with endometriosis who do not plan in vitro fertilization in near future.